The OEIS is supported by the many generous donors to the OEIS Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A114525 Triangle of coefficients of the Lucas (w-)polynomials. 29
 2, 0, 1, 2, 0, 1, 0, 3, 0, 1, 2, 0, 4, 0, 1, 0, 5, 0, 5, 0, 1, 2, 0, 9, 0, 6, 0, 1, 0, 7, 0, 14, 0, 7, 0, 1, 2, 0, 16, 0, 20, 0, 8, 0, 1, 0, 9, 0, 30, 0, 27, 0, 9, 0, 1, 2, 0, 25, 0, 50, 0, 35, 0, 10, 0, 1, 0, 11, 0, 55, 0, 77, 0, 44, 0, 11, 0, 1, 2, 0, 36, 0, 105, 0, 112, 0, 54, 0, 12, 0, 1, 0 (list; table; graph; refs; listen; history; text; internal format)
 OFFSET 0,1 COMMENTS Unsigned version of A108045. The row reversed triangle is A162514. - Paolo Bonzini, Jun 23 2016 LINKS G. C. Greubel, Rows n = 0..100 of triangle, flattened B. Johnson, Fibonacci numbers and matrices, 2009. Jong Hyun Kim, Hadamard products and tilings, JIS 12 (2009) 09.7.4. M. Pétréolle, Characterization of Cyclically Fully commutative elements in finite and affine Coxeter Groups, arXiv preprint arXiv:1403.1130 [math.GR], 2014. Eric Weisstein's World of Mathematics, Fibonacci Polynomial Eric Weisstein's World of Mathematics, Lucas Polynomial FORMULA From Peter Bala, Mar 18 2015 The Lucas polynomials L(n,x) satisfy the recurrence L(n+1,x) = x*L(n,x) + L(n-1,x) with L(0,x) = 2 and L(1,x) = x. O.g.f.: Sum_{n >= 0} L(n,x)*t^n = (2 - x*t)/(1 - t^2 - x*t) = 2 + x*t + (x^2 + 2)*t^2 + (3*x + x^3)*t^3 + .... L(n,x) = trace( [ x, 1; 1, 0 ]^n ). exp( Sum_{n >= 1} L(n,x)*t^n/n ) = Sum_{n >= 0} F(n+1,x)*t^n, where F(n,x) denotes the n-th Fibonacci polynomial. (see Appendix A3 in Johnson). exp( Sum_{n >= 1} L(n,x)*L(2*n,x)*t^n/n ) = 1/( F(1,x)*F(2*x)*F(3,x) ) * Sum_{n >= 0} F(n+1,x)*F(n+2,x)*F(n+3,x)*t^n. exp( Sum_{n >= 1} L(3*n,x)/L(n,x)*t^n/n ) = Sum_{n >= 0} L(2*n + 1,x)*t^n. L(n,1) = Lucas(n) = A000032(n); L(n,4) = Lucas(3*n) = A014448(n); L(n,11) = Lucas(5*n) = A001946(n); L(n,29) = Lucas(7*n) = A087281(n); L(n,76) = Lucas(9*n) = A087287(n); L(n,199) = Lucas(11*n) = A089772(n). The general result is L(n,Lucas(2*k + 1)) = Lucas((2*k + 1)*n). (End) From Jeremy Dover, Jun 10 2016: (Start) Read as a triangle T(n,k), n >= 0, n >= k >= 0, T(n,k) = (Binomial((n+k)/2,k) + Binomial((n+k-2)/2,k))*(1+(-1)^(n-k))/2. T(n,k) = A046854(n-1,k-1) + A046854(n-1,k) + A046854(n-2,k) for even n+k with n+k > 0, assuming A046854(n,k) = 0 for n < 0, k < 0, k > n. T(n,k) is the number of binary strings of length n with exactly k pairs of consecutive 0's and no pair of consecutive 1's, where the first and last bits are considered consecutive. (End) From Peter Bala, Sep 03 2022: (Start) L(n,x) = 2*(i)^n*T(n,-i*x/2), where i = sqrt(-1) and T(n,x) is the n-th Chebyshev polynomial of the first kind. d/dx(L(n,x)) = n*F(n,x), where F(n,x) denotes the n-th Fibonacci polynomial. Let P_n(x,y) = (L(n,x) - L(n,y))/(x - y). Then {P_n(x,y): n >= 1} is a fourth-order linear divisibility sequence of polynomials in the ring Z[x,y]: if m divides n in Z then P_m(x,y) divides P_n(x,y) in Z[x,y]. P_n(1,1) = A045925(n); P_n(1,4) = A273622; P_n(2,2) = A093967(n). L(2*n,x)^2 - L(2*n-1,x)*L(2*n+1,x) = x^2 + 4 for n >= 1. Sum_{n >= 1} L(2*n,x)/( L(2*n-1,x) * L(2*n+1,x) ) = 1/x^2 and Sum_{n >= 1} (-1)^(n+1)/( L(2*n,x) + x^2/L(2*n,x) ) = 1/(x^2 + 4), both valid for all nonzero real x. (End) From Peter Bala, Nov 18 2022: (Start) L(n,x) = Sum_{k = 0..floor(n/2)} (n/(n-k))*binomial(n-k,k)*x^(n-2*k) for n >= 1. For odd m, L(n, L(m,x)) = L(n*m, x). For integral x, the sequence {u(n)} := {L(n,x)} satisfies the Gauss congruences: u(m*p^r) == u(m*p^(r-1)) (mod p^r) for all positive integers m and r and all primes p. Let p be an odd prime and let 0 <= k <= p - 1. Let alpha_k = the p-adic limit_{n -> oo} L(p^n,k). Then alpha_k is a well-defined p-adic-integer and the polynomial L(p,x) - x of degree p factorizes as L(p,x) - x = Product_{k = 0..p-1} (x - alpha_k). For example, L(5,x) - x = x^5 + 5*x^3 + 4*x = x*(x - A269591)*(x - A210850)*(x - A210851)*(x - A269592) in the ring of 5-adic integers. (End) The formula for L(n,x) given in the first line of the preceding section, with L(0, x) = 2, is rewritten L(n, x) = Sum_{k = 0..floor(n/2)} A034807(n, k)*x^(n - 2*k). See the formula by Alexander Elkins in A034807. - Wolfdieter Lang, Feb 10 2023 EXAMPLE 2, x, 2 + x^2, 3*x + x^3, 2 + 4*x^2 + x^4, 5*x + 5*x^3 + x^5, ... give triangle n\k 0 1 2 3 4 5 6 7 8 9 10 ... 0: 2 1: 0 1 2: 2 0 1 3: 0 3 0 1 4: 2 0 4 0 1 5: 0 5 0 5 0 1 6: 2 0 9 0 6 0 1 7: 0 7 0 14 0 7 0 1 8: 2 0 16 0 20 0 8 0 1 9: 0 9 0 30 0 27 0 9 0 1 10: 2 0 25 0 50 0 35 0 10 0 1 n\k 0 1 2 3 4 5 6 7 8 9 10 ... .... reformatted by Wolfdieter Lang, Feb 10 2023 MAPLE Lucas := proc(n, x) option remember; if n=0 then 2; elif n =1 then x ; else x*procname(n-1, x)+procname(n-2, x) ; end if; end proc: A114525 := proc(n, k) coeftayl(Lucas(n, x), x=0, k) ; end proc: seq(seq(A114525(n, k), k=0..n), n=0..12) ; # R. J. Mathar, Aug 16 2019 MATHEMATICA row[n_] := CoefficientList[LucasL[n, x], x]; Table[row[n], {n, 0, 12}] // Flatten (* Jean-François Alcover, Aug 11 2018 *) CROSSREFS Cf. A108045 (signed version). Cf. A034807, A162514. Cf. Sequences L(n,x): A000032(x = 1), A002203 (x = 2), A006497 (x = 3), A014448 (x = 4), A087130 (x = 5), A085447 (x = 6), A086902 (x = 7), A086594 (x = 8), A087798 (x = 9), A086927 (x = 10), A001946 (x = 11), A086928 (x = 12), A088316 (x = 13), A090300 (x = 14), A090301 (x = 15), A090305 (x = 16), A090306 (x = 17), A090307 (x = 18), A090308 (x = 19), A090309 (x = 20), A090310 (x = 21), A090313 (x = 22), A090314 (x = 23), A090316 (x = 24), A087281 (x = 29), A087287 (x = 76), A089772 (x = 199). Sequence in context: A321731 A358135 A212357 * A127672 A294168 A299196 Adjacent sequences: A114522 A114523 A114524 * A114526 A114527 A114528 KEYWORD nonn,tabl,easy AUTHOR Eric W. Weisstein, Dec 06 2005 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified February 27 16:21 EST 2024. Contains 370378 sequences. (Running on oeis4.)